Testing Pecking Order Prediction of Financing Choices in NEPSE Listed Non-Financial Companies of Nepal - Subedi, Kapil Dev (Saptagandaki Journal, 2022)
In a financial market with information, agency and contract enforcement problem, partially informed firms have difficulty to access in capital markets and they face some restrictions to get adequate external capital at similar cost of their internal funds. Hence, these firms display the preferential order of financing choices, for example; first they invest internal funds, second debt capital and equity as last resort. However, such preferences of financing order commonly known as Pecking Order are not similar in all cases due to the nature of firms, their financial health, borrowing capacity, and functioning of capital markets. Under this backdrop, this study attempted to test this Pecking Order Hypothesis (POH) in financing decisions of Nepalese firms. Moreover, it tried to examine the effect of firm's borrowing capacity, informational efficiency, financial risk, operating growth, taxes and internal profitability on pecking order financing preferences of firms. It used quantitative approach of analysis to examine the financing behavior of 16 non-financial NEPSE listed companies. Descriptive and inferential statistics i.e. Pooled Ordinary Least Square (OLS) regression approach was used to test the hypothesis and data comprised unbalanced panel (n=262 observations) obtained from annual financial reports of sampled companies. The study results revealed that firm specific financial risk including borrowing capacity, operating growth, internal profitability and information efficiency have significant impact in firms' financing polices. Firms have preferences to use debts instead of equity when they face financing deficiency and these preferences are prominent when firms plummet in severe financing constraints. Hence, this study concluded that a firm's capacity to trade off its financial risk with some firm specific attributes outlined the most of the financing policies of Nepalese enterprises. These financial risks absorption capacity of the firms could be considerably improved if firms improved their profitability, sales growth, information efficiency and spare borrowing capacity; hence, these factors are imperative to design the optimal capital structure of firms and maximize their values.